Molecular forces driving protein complexation of lentil and whey proteins: Structure-function relationships of trehalose-conjugated protein complexes on protein digestibility and solubility - Mohammad, Alrosan (2024)
Plant-based proteins are often associated with a range of health benefits. Most research primarily investigates pea and soy proteins, while lentil proteins received minimal attention. This study evaluates the effect of protein complexation (using the pH-shifting technique) coupled with trehalose conjugation on lentil and whey proteins. The protein structures after the modification were analysed using spectroscopic methods: Fourier-transform infrared, ultraviolet spectra, and fluorescence spectra. The amide group I, conformation protein, and tertiary structure of the trehalose-conjugated lentil-whey protein complexes (T-LWPs) showed significant changes (P < 0.05). Moreover, the surface properties (surface hydrophobicity and charges) of T-LWPs were significantly modified (P < 0.05), from 457 to 324 a.u and from 36 to −40 mV, respectively. Due to these modifications on the protein structures, the protein digestibility (80–86%) and water solubility (90–94.5%) of T-LWPs increased significantly (P < 0.05) with the increase in the trehalose concentration, from 0 (control) to 5% (w/w), respectively. This study suggested that coupling protein complexation and trehalose conjugation can enhance the overall properties of lentil-based protein complexes. With this enhancement, more opportunities in the utilisation of lentils are to be expected.